Diseases in mung bean with the spreading and dibbling planting system in Banyumas Regency, Central Java, Indonesia - Dhika Kintania Primandani; Hagia Sophia Khairani; Tri Asmira Damayanti (Agrovigor, 2025)
Mung bean is Indonesia's important legume crop after soybean and peanut, and it can be grown as a primary crop or an intercrop. The purpose of this study was to compare disease development and yield on mung bean fields grown under a spreading and dibbling cropping system in Kedungwringin Village, Jatilawang District, Banyumas Regency, Central Java. Data was collected from farmers through interviews and weekly disease observation in six mung bean fields. The type of disease, disease incidence, and severity were also determined using data obtained directly from the field. The study discovered five fungi and virus: powdery mildew (Erysiphe sp.), stem rot (Sclerotium rolfsii), leaf rust (Uromyces sp.), leaf spot (Cercospora sp.), and yellow mosaic disease (Begomovirus). The incidence of such diseases was ranging from 1% up to 85%, with the yellow mosaic disease having a very low incidence. There is no significant difference of disease intensity on both system. Leaf spot was the major disease with severity increasing gradually from 11.11% to 43.17%. Several insect pests and predators were discovered in fields. Considering the higher pod production in response to the disease occurrence, the dibble cropping system is recommended as the better mung bean farming strategy.